Implementasi Teknologi Digital dan TIK dalam Pembelajaran Inovatif Berorientasi Kreativitas - Arysespajayadi; I Gede Purwana Edi Saputra (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
The development of digital technology and Information and Communication Technology (ICT) has driven a shift in the learning paradigm toward more innovative approaches oriented to the development of students’ creativity. This study aims to analyze the implementation of digital technology and ICT in innovative learning and its contribution to enhancing students’ creativity. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and document analysis. The research subjects include teachers and students involved in digital technology–based learning. The results indicate that the use of digital technology and ICT is able to create learning environments that are more interactive, contextual, and collaborative. Students become more active in exploring ideas, expressing opinions, and producing creative work. However, the implementation of technology-based learning still faces several challenges, such as limited infrastructure, variations in students’ digital literacy, and teachers’ readiness. This study concludes that the appropriate integration of digital technology and ICT can serve as an effective strategy to support innovative learning oriented toward creativity.